3/(4g)=(7-a)/g
multiplying by 4g
3=4(7-a)
3=28-4a
adding -28
-25=-4a
dividingby -4
a=6 1/4
2007-01-02 08:49:38
·
answer #1
·
answered by raj 7
·
0⤊
0⤋
All you need to to is get a by itself.
First, to make it LOOK better, switch sides:
(7-a)g = 3/(4/g)
Next, because 3/(4/g) looks bad too, make it g*3/4
so (7-a)*g = g*3/4
Divide both sides by g and you get
7-a = 3/4
Finally, subtract 7 from both sides:
-a = 3/4 - 7 = -6 1/4
or
a = 6 1/4
2007-01-02 08:48:09
·
answer #2
·
answered by firefly 6
·
0⤊
0⤋
a=6.25
3/(4/g)=(7-a)g
(3/4)g=(7-a)g
cancelling out the g's,
3/4=7-a
a=7-3/4
= 6 1/4 or 6.25
hope this is right
2007-01-02 08:52:49
·
answer #3
·
answered by purpleraiment 2
·
0⤊
0⤋
See-
(7-a)g= 3/(4/g)
Cross out both the g's.
So, it is=
7-a= 3/4
Now, solve 3/4 which is 0.75
Now, it is-
7-a= 0.75
And at the end,
a= 6.5
Solve it at last and you finally get- 6 1/2
The answer is 6 1/2 and in decimals, it is 6.5
2007-01-02 09:03:00
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
Oh, well 3/(4/g) = (3g)/4 = (7-a)g.
So, the g's cancel out, giving you 3/4 = 7-a.
So, a=7-(3/4) = 6 1/4 = 6.25.
2007-01-02 08:48:07
·
answer #5
·
answered by yljacktt 5
·
0⤊
0⤋
first change 3/(4/g) to 3g/4 then divide each side by g to get 3/4=7-a then subtract 7 from each side to get a=6 1/4
2007-01-02 08:47:15
·
answer #6
·
answered by clock 2
·
0⤊
0⤋